Forest bathing environments in virtual reality: enhancing well-being through immersive nature experiences - Almeida, Raquel Simões de (2023)
The present study proposes an innovative approach to promote wellbeing by developing forest bathing environments in virtual reality (VR). Forest bathing, a practice rooted in traditional Japanese culture, involves immersing oneself in a forest atmosphere to enhance physical and mental health. VR technology enables the opportunity to recreate and simulate these natural environments, allowing individuals to experience the benefits of forest bathing regardless of their physical location and limitations of physical access to natural environments. This study aims to design and evaluate the effectiveness of a VR forest bathing environment in improving well-being, stress reduction, and overall relaxation.